Depressive Symptoms, Sleep Quality and Diet During the 2019 Novel Coronavirus Epidemic in China: A Survey of Medical Students - Xie, Jianping; Li, Xia; Luo, Haiyun; He, Liu; Bai, Yufan; Zheng, Fuyun; Zhang, Lanchun; Ma, Jiaqing; Niu, Zhiqiang; Qin, Yubing; Wang, Ling; Ma, Wenjie; et al. (Frontiers in Public Health, 2021)
The psychological condition of medical students may be influenced by the 2019 novel coronavirus (COVID-19) outbreak. This study investigated the prevalence and influencing factors of depressive symptoms, poor sleep quality and poor diet in students at Kunming Medical University during the early part of the COVID-19 outbreak. A cross-sectional study was used from a questionnaire survey in February 2020. Of a total of 1026 study participants, the prevalence of depressive symptoms, poor sleep quality, and poor diet was, respectively, 22.4%, 33.2%, and 17.4%. Male students and students with a low degree of focus on COVID-19 had a high risk of depressive symptoms. A high percentage of females and students in the fifth grade, as well as students with high levels of concern about the negative impact of COVID-19 on their education or employment, comprised those with poor sleep quality. Students in the fifth grade and students with high levels of concern about the negative impact of COVID-19 on their education or employment were more likely to report poor diet. This study suggests the importance of monitoring medical students’ depressive state during the COVID-19 outbreak, and universities are encouraged to institute policies and programs to provide educational counseling and psychological support to help students to cope with these problems.